Long-term results of distal oblique bundle reinforcement for treatment of chronic bidirectional instability of the distal radioulnar joint. (December 2022) - Verbeek, Diederik O.; Wilssens, Nicholas O. J.; ten Bosch, Jan A.; Hannemann, Pascal F. W.
Distal oblique bundle (DOB) reinforcement for treatment of post-traumatic bidirectional instability of the distal radioulnar joint (DRUJ) has previously been reported. The objective of the current study was to assess the incidence of symptomatic graft failure and the need for secondary wrist procedures at a longer follow-up in an updated patient cohort of 27 patients with 28 DOB reinforcement procedures. Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) and patient-rated wrist/hand evaluation (PRWHE) outcome measures were also evaluated. At median 82 months follow-up, pre- to postoperative QuickDASH score improved from a mean of 62 (SD 14) to 31 (SD 22) ( p < 0.01) and PRWHE score from a mean of 67 (SD 17) to 34 (SD 23) ( p < 0.01). Symptomatic graft failure with resultant painful DRUJ instability occurred in four out of 28 procedures, which was better than the published results of alternative surgical options for DRUJ instability. DOB reinforcement presents a relatively safe, effective and durable method for treatment of post-traumatic DRUJ instability. Level of evidence: III